Field-conditioned alfalfa hay as it affects the winter performance of weaned heifer calves - Smith, E.F.; Richardson, D.; Fairbanks, G.E.; Thierstein, G.E.; Follis, D.L.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Through cooperative efforts of the Departments of Agronomy and Agricultural Engineering, fourth-cutting alfalfa hay was made available to winter-feed weaned heifer calves. The object of the experiment was to determine the effects of various field-conditioned alfalfa hays on the winter performance of heifer calves.
Keywords: Beef; Alfalfa hay; Performance; Heifer calves